Seasonal variations in the onset of retinal vein occlusion. - Hayreh, S. S. (1992)
Seasonal variation in the development of retinal vein occlusion in 1003 consecutive patients with various types of retinal vein occlusion was studied prospectively from 1973 to 1990. No seasonal variation in the onset of any type or combination of types of retinal vein occlusion was found. This refutes previous reports of such seasonal variation, which were based on small retrospective series.